TINJAUAN HUKUM PERJANJIAN PENGANGKUTAN DARAT PUPUK UREA BERSUBSIDI (Studi pada PT. Pupuk Iskandar Muda) - Teuku Rizky Radhian (JURNAL CIVIL LAW USU, 2013)
Abstrak : Subsidized fertilizer are the procurement and distribution fertilizer that subsidies from the government to the needs of farmers  based on the government programs in agriculture. For the distribution the producers working with transport companies, therefore made ​​transport agreement between the producers and the transport companies prior to the transportation of subsidized fertilizer. Regarding the law of the land transport rules regulated in Act Number 22 year 2009 on Road Traffic and Transport. Kata kunci : Perjanjian, Pengangkutan, Darat